Dampak Prosedural Bank ASI terhadap Tatanan Kemahraman: Analisis Istinbath Hukum Islam di Era Modern - Imam Maliki; Yustika Wardah Hayya (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2026)
This study aims to analyze the procedural impact of human milk banks on the legal certainty of breastfeeding kinship (radha‘ah) and to offer a sharia-compliant operational framework. The background problem is the emergence of modern milk banks that implement anonymity and milk pooling from multiple donors, potentially obscuring the identity of mahram relationships and threatening the validity of future marriages. This research employs a library research method with a qualitative approach. Data collection was conducted through systematic searches of journal articles (2021–2026), classical Islamic jurisprudence books from the four schools of thought, and regulatory documents (Government Regulation No. 28/2024, MUI Fatwa No. 28/2013).. The findings indicate that the main issue is not the absolute permissibility or prohibition of milk banks, but rather the absence of binding procedural standards, particularly in documenting donor identities, recording the number of feedings, and supervising sharia compliance. Current Indonesian regulation (GR No. 28/2024) recognizes milk donation but does not technically regulate the recording of mahram relationships, creating legal uncertainty. This study contributes by proposing the necessity of a national breastfeeding recording standard recognized by religious courts, and by encouraging integration between health and religious authorities. The policy implication is the need to revise GR No. 28/2024 by adding sanction clauses and mandatory donor-recipient identity recording mechanisms. Further research is recommended to conduct empirical studies in operating milk banks and to analyze jurisprudence on marriage annulment due to unrecognized breastfeeding kinship.